Gestational diabetes screening – OGTT or HAPO. (7th June 2011) - Burrell, C; Kropiwnicka, Z; Howard, R; Casey, E; Phillips, L
Abstract : The National Institute for Health and Clinical Excellence (NICE) Diabetes Guideline (2008) recommends more screening for gestational diabetes in the UK. With increase in obesity, more women delaying childbirth, thus entering pregnancy with co-morbidities, and more ethnic minorities (CEMACH Report 2006–2008) results is an increase in gestational diabetes. Oral glucose tolerance test (OGTT) remains the preferred screening test, but the hyperglycemia and adverse pregnancy outcome (HAPO) Study (2008) offers another option. Method: This retrospective audit compared fetal and maternal outcome using the OGTT and HAPO Screening methods. The OGTT Screen was positive if blood results show – fasting >5.6 and 2 h >7.8 mmol/l (Group 1) and HAPO positive if – fasting >5.1 and 2 h >8.5 mmol/l (Group 2). Data was obtained from the computer records and Diabetes Registry. Screening was done using the NICE Guideline. Results: During 1 January 2009 to 31 December 2009 at Barking, Havering & Redbridge University Hospital, Essex, UK. Positive OGTT (Group 1)=386 women, and positive HAPO (Group 2)=312 women. The table 1 compares pregnancy outcome in both groups. Discussion: The HAPO screening missed 74/386 (19.17%) of women. The OGTT screening picked up more high-risk women with increase fetal and maternal morbidity.